2021
DOI: 10.1007/s00330-021-08009-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of radiomics and machine learning in breast ultrasound: a multicenter study for differential diagnosis of benign and malignant lesions

Abstract: Objectives We aimed to assess the performance of radiomics and machine learning (ML) for classification of non-cystic benign and malignant breast lesions on ultrasound images, compare ML’s accuracy with that of a breast radiologist, and verify if the radiologist’s performance is improved by using ML. Methods Our retrospective study included patients from two institutions. A total of 135 lesions from Institution 1 were used to train and test the ML model wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 30 publications
3
30
2
Order By: Relevance
“…21 In our study, the selected ML pipeline (DNN-RFE) based on ABVS radiomics also showed satisfactory discrimination performance in the testing cohort, with the AUC, sensitivity, specificity, and accuracy of 0.954, 95.2%, 83.3%, and 88.9%, respectively. Interestingly, Romeo et al 30 used the ML algorithm (RF) based on US radiomics to distinguish benign and malignant breast lesions with an accuracy of 82% and an AUC of 0.82, which is lower than that of our study (88.9% and 0.954), although our study focuses on more challenging lesions (BI-RADS 4). The possible reason is that the three ABVS images (axial, sagittal, and coronal) may provide more radiomic features and better represent tumor heterogeneity than a single US Thus, ABVS images are indeed suitable for radiomics and ML methods, and may provide clinical decision support for the management and treatment of breast cancer.…”
Section: Test the Predictive Performance Of Selected ML Modelscontrasting
confidence: 72%
“…21 In our study, the selected ML pipeline (DNN-RFE) based on ABVS radiomics also showed satisfactory discrimination performance in the testing cohort, with the AUC, sensitivity, specificity, and accuracy of 0.954, 95.2%, 83.3%, and 88.9%, respectively. Interestingly, Romeo et al 30 used the ML algorithm (RF) based on US radiomics to distinguish benign and malignant breast lesions with an accuracy of 82% and an AUC of 0.82, which is lower than that of our study (88.9% and 0.954), although our study focuses on more challenging lesions (BI-RADS 4). The possible reason is that the three ABVS images (axial, sagittal, and coronal) may provide more radiomic features and better represent tumor heterogeneity than a single US Thus, ABVS images are indeed suitable for radiomics and ML methods, and may provide clinical decision support for the management and treatment of breast cancer.…”
Section: Test the Predictive Performance Of Selected ML Modelscontrasting
confidence: 72%
“…One major concern should be noted that there were too many features involved in their modeling compared to ours (60 vs. 14). The most convincing method to identify whether the trained model is overfitted is externally testing it on unseen data obtained from another institution [ 29 , 30 ]. The results of our external test suggest there was a moderate overfitting in our models, even if only 14 features were used as classifier inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasonography is the one of most common imaging technique used to detect and distinguish benign and malignant breast lesions, it is difficult to accurately and stably identify some lesions with the naked eye. Recently, many studies have explored the potential of ultrasound radiomics to aid in the detection and differentiation of lesions ( 9 , 17 20 ) ( Table 1 ).…”
Section: Ultrasound Radiomics In the Breast Diagnosismentioning
confidence: 99%
“…This study confirmed that the DLR model had equal or better diagnostic performance compared to radiologists on a test dataset with 120 breast lesions (AUC = 0.913 vs 0.728-0.845, p = 0.01-0.14). Subsequently, several studies have shown that ultrasound radiomics based on 2D-US images has good performance in identifying benign from malignant breast lesion, with AUCs ranging from 0.817-0.943 ( 9 , 17 19 ). Additionally, studies have shown that the classification performance of the AI model may be affected by adjusting the ROI as different inputs of the model.…”
Section: Ultrasound Radiomics In the Breast Diagnosismentioning
confidence: 99%
See 1 more Smart Citation